2022
DOI: 10.1038/s41565-022-01182-5
|View full text |Cite|
|
Sign up to set email alerts
|

Direct patterning of colloidal quantum dots with adaptable dual-ligand surface

Abstract: Colloidal quantum dots (QDs) stand at the forefront of a variety of photonic applications given their narrow spectral bandwidth and near-unity luminescence e ciency. Integrating desired forms of QD lms into photonic systems without compromising their optical or transport characteristics is the key to bridging the gap between expectations and outcomes. Here, we devise a dual-ligand passivation system comprising photocrosslinkable ligands and dispersing ligands to enable QDs to be universally compatible with sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 50 publications
0
54
0
Order By: Relevance
“…We showed that after systematic surface property engineering, ILANs were suitable for various industrially adapted patterning techniques, including direct optical lithography of functional inorganic nanomaterials (DOLFIN) 19,20 and inkjet printing, to design luminescent microscale structures with a spatial resolution down to 2 μm and a line edge roughness of 200 nm. Recently, many NC patterning strategies have been used to fabricate QLEDs with high performance [21][22][23] . The ability to reliably obtain ILANs along with the development of various material-adapted patterning techniques creates a versatile platform for next-generation QD-based optoelectronic devices.…”
mentioning
confidence: 99%
“…We showed that after systematic surface property engineering, ILANs were suitable for various industrially adapted patterning techniques, including direct optical lithography of functional inorganic nanomaterials (DOLFIN) 19,20 and inkjet printing, to design luminescent microscale structures with a spatial resolution down to 2 μm and a line edge roughness of 200 nm. Recently, many NC patterning strategies have been used to fabricate QLEDs with high performance [21][22][23] . The ability to reliably obtain ILANs along with the development of various material-adapted patterning techniques creates a versatile platform for next-generation QD-based optoelectronic devices.…”
mentioning
confidence: 99%
“…Semiconductor alloying is an effective and versatile tool for customizing the intrinsic physical properties of materials such as the bulk bandgap, effective mass of charge carriers, and lattice parameter on demand. Reducing the dimension of semiconductor alloys to the nanoscale permits additional control of the distribution of charge carriers and their dynamics, which enables us to achieve almost arbitrary control of optical and electrical characteristics of materials. Nanocrystals (NCs) made of semiconductor alloys, whose physical dimensions allow for efficient charge carrier recombination and cost-effective solution processing, have attracted considerable attention as next-generation photon emitters in a wide range of applications, including tunable lasers, light-emitting diodes, and luminescent solar concentrators. …”
mentioning
confidence: 99%
“…Although full-color, high-resolution QLEDs could be demonstrated based on photolithography, the procedure to minimize the damages is exceedingly complicated [ 142 , 143 ]. Recently, a direct QD patterning method has been reported, which is a technique for patterning QDs based on photolithography but without the PR processes [ 131 , 144 , 145 , 146 , 147 , 148 ]. It can be achieved by adopting light-responsive ligands onto the surface of QDs, which chemically binds QDs upon illumination to firmly hold the pattern against the following wash-out step.…”
Section: Qled Frontplane Technologymentioning
confidence: 99%
“…UV exposure to the modified QD film induces a chemical reaction between azides and the alkyl chain of QD ligands, resulting in a crosslinked QD layer, as shown in Figure 5 c. Full-color, high-resolution QD patterns of >1400 PPI were demonstrated, and red crosslinked QLEDs exhibited an EQE of 14.6%. In 2022, Hahm et al proposed direct patterning with dual ligands composed of dispersing ligands and photo-cross-linkable ligands to maintain the PL QY during photo-crosslinking [ 148 ]. As a result, they successfully demonstrated full-color QLED arrays employing the patterned QD films in a high resolution of >15000 PPI without a performance loss.…”
Section: Qled Frontplane Technologymentioning
confidence: 99%